Parenting stress and needs for social support in mothers and fathers of deaf or hard of hearing children - Amélie Marie; Laëtitia Clabaut; Marjolaine Corbeil; Clémence Vanlerberghe; Catherine Vincent-Delorme; Barbara Le Driant (Frontiers in Psychology, 2023)
IntroductionHearing parents of deaf or hard of hearing (DHH) children may experience parenting stress and social support could be a buffer to this stress. Differences in levels of these two indicators may exist between mothers and fathers. This study focuses on the parenting stress and social support needs of mothers and fathers of DHH children.MethodsTwenty-seven French parental couples of DHH children completed the Parenting Stress Index and the Family Needs Survey, a questionnaire on social support needs.ResultsTheir overall stress scores showed no difference, but subdomain scores show that mothers and fathers are more stressed by the child’s hyperactivity, and fathers by the child’s adaptability, than parents of children with normal hearing. Mothers are more stressed than fathers by role restriction; they feel less free because of their parenting role. Fathers have a lower quality of attachment to their child than mothers. Parents have a high social support need, especially for obtaining information about their child’s individual characteristics and health situation. The ranking of mothers and fathers in the top 10 needs reveals different needs profiles. Parenting stress profiles show that mothers and fathers with higher-than-normal stress levels have a greater overall need for social support than mothers and fathers with lower than normal stress levels.DiscussionThis study highlights the value of assessing parenting stress and social support needs in parents of DHH children for a better understanding of their situation in research and its clinical implications, as well as the importance of differentiating outcomes for mothers and fathers.